Digital tools to enhance adherence to cervical cancer prevention practices: systematic review - Ayagyoz Umbetzhanova; Adina Kusniyeva; Gulmira Derbissalina; Almabayeva Aigul; Çigdem Çaglayan; Gulnur Tanbayeva; Vitaliy Koikov; Naila Toktarova; Zhanagul Bekbergenova (Frontiers in Public Health, 2026)
Background Human papillomavirus (HPV) vaccination and regular cervical screening are fundamental pillars of the World Health Organization (WHO) strategy to eliminate cervical cancer. While conventional one-way digital notifications moderately support preventive uptake, the specific behavioral impact of two-way, interactive patient-facing digital assistants-such as conversational artificial intelligence (AI) and gamified health applications-warrants rigorous, isolated synthesis. Objective To systematically assess whether patient-facing interactive digital assistants are associated with improved initiation and completion of HPV vaccination and cervical cancer screening, strictly distinguishing between formative usability evidence and clinical effectiveness. Methods Following PRISMA 2020 guidelines and PROSPERO registration (CRD420261333651), six academic databases were systematically searched (January 1, 2016–February 10, 2026). Eligible interventions were limited to interactive patient-facing digital tools. Data synthesis utilized a structured narrative approach, applying the Mixed Methods Appraisal Tool (MMAT 2018) for individual domain risk of bias and GRADE principles for evidence certainty. Results The synthesis included 14 reports representing 13 independent studies. Formative evaluations indicated high usability and user acceptability. Within behavioral trials, conversational AI chatbots showed promising effects for short-term increases in HPV vaccine appointment booking (Moderate certainty). However, multi-dose series completion remained severely constrained by high attrition rates (Low certainty). For secondary prevention, theory-based apps were associated with enhanced short-term cytology uptake (Moderate certainty). A serious game correlated with a higher diagnostic rate of cervical precancer (CIN2+); however, profound uncontrolled confounding limits causal attribution. Conclusion Interactive patient-facing digital assistants may improve short-term appointment scheduling and screening participation. Nevertheless, the current literature is heavily constrained by self-selection, attrition, and the inability to isolate the effects of multicomponent interventions. Future pragmatic trials are essential to replicate these findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420261333651 , CRD420261333651.